The Impact of Digital Technologies on the Companies’ Strategic Management - Goi, V.; Ahieieva, Iryna; Mamonov, K.; Pavliuk, S.; Dligach, A.; Агєєва, Ірина Вікторівна (Нью-Делі : 2023, 2023)
EN: Thanks to digital technologies, companies ensure competitiveness in the market, acquire new sources of revenue and transform management strategies. The companies have gained more opportunities to enter global markets and access goods and services in any country worldwide. These opportunities change their strategic development priorities and enable the scaling up of their activities. The article aimed to analyze the impact of digital technologies on the strategic management of companies. Methodology. The authors utilize a statistical analysis approach to assess changes in the strategic management of companies in the context of digital technology integration and solutions. They analyze secondary data from a survey of 414 IT directors in 2020 regarding the strategic priorities in the digitalization era. The research results confirm the shift in strategic priorities of enterprises (during and after the pandemic) due to the active integration of digital technologies. The authors identify the trends of increasing investments in direct digital business transformation and digital transformation expenditures, from $1,6 trillion in 2022 to $3,4 trillion in 2026. Starting in 2020, digital transformation and changes in business processes, operational efficiency improvement, optimization of customer experience, and support for remote work have become key strategic priorities for businesses. The need for enhancing cybersecurity and protection, optimizing digital employee experience, improving workforce productivity, and increasing profitability are identified among important business initiatives. The following challenges and opportunities for enterprises during the implementation of digital technologies have been identified: (1) data becomes a foundation of competitiveness; (2) development of the Internet of Things allows large companies to enter markets and expand internationally; (3) digitalization of business and economic sectors, active development of new segments (biotechnology, digital communications, medical technologies, etc.); (4) virtualization of IT systems as physical infrastructure; (5) the use of artificial intelligence for facilitating strategic decision-making through processing and analysis of large volumes of data. UA: Завдяки цифровим технологіям компанії забезпечують конкурентоспроможність на ринку, отримують нові джерела доходу та трансформують стратегії управління. Компанії отримали більше можливостей для виходу на глобальні ринки та доступу до товарів і послуг у будь-якій країні світу. Ці можливості змінюють їхні стратегічні пріоритети розвитку та дозволяють розширити їхню діяльність. Метою статті було проаналізувати вплив цифрових технологій на стратегічне управління компаніями. Методологія. Автори використовують підхід статистичного аналізу для оцінки змін у стратегічному управлінні компаніями в контексті інтеграції цифрових технологій та рішень. Вони аналізують вторинні дані опитування 414 IT-директорів у 2020 році щодо стратегічних пріоритетів в епоху цифровізації. Результати дослідження підтверджують зміну стратегічних пріоритетів підприємств (під час та після пандемії) через активну інтеграцію цифрових технологій. Автори визначають тенденції зростання інвестицій у пряму цифрову трансформацію бізнесу та витрат на цифрову трансформацію з $1,6 трлн у 2022 році до $3,4 трлн у 2026 році. Починаючи з 2020 року цифрова трансформація та зміни в бізнес-процесах, підвищення операційної ефективності, оптимізація клієнтського досвіду та підтримка віддаленої роботи стали ключовими стратегічними пріоритетами для бізнесу. Серед важливих бізнес-ініціатив визначено потребу в посиленні кібербезпеки та захисту, оптимізації цифрового досвіду співробітників, покращенні продуктивності робочої сили та підвищенні прибутковості. Виявлено наступні виклики та можливості для підприємств під час впровадження цифрових технологій: (1) дані стають основою конкурентоспроможності; (2) розвиток Інтернету речей дозволяє великим компаніям виходити на ринки та виходити на міжнародний рівень; (3) цифровізація бізнесу та секторів економіки, активний розвиток нових сегментів (біотехнології, цифрові комунікації, медичні технології тощо); (4) віртуалізація ІТ-систем як фізичної інфраструктури; (5) використання штучного інтелекту для полегшення прийняття стратегічних рішень шляхом обробки та аналізу великих обсягів даних.
Вплив цифрових технологій на стратегічне управління компаніями
Keywords: digital technologies; digital business models; digital business transformation; corporate governance; strategic management; digital business strategies; цифрові технології; цифрові бізнес-моделі; цифрова трансформація бізнесу; корпоративне управління; стратегічний менеджмент